Microplastics in sea surface waters in the Southern Bight of the North Sea - Hoehn, Danja P.; McGoran, Alexandra R.; Barry, Jon; Russell, Josie; Nicolaus, E. E. Manuel; Bakir, Adil (Frontiers in Marine Science, 2024)
Microplas c pollu on in the marine environment is of concern, with evidence of harmful effects on marine biota and ecosystems. There is s ll a knowledge gap of the mass of plas cs supplied to the ocean and plas cs observed in the ocean, indica ng a missing sink. Therefore, baseline and monitoring data are needed to inform policy and regulatory measures. The goal of this study was to collect harmonized data of microplas cs from the surface of the ocean using the Neuston Microplas c Catamaran. This study shows that the surface water of the coastal ocean in the North Sea holds/sustains high concentra ons of microplas c which exceed previously recorded measurements from the North-East Atlan c and Sco sh Waters, indica ng that the total stock of plas cs might be much higher than previously determined. Microplas cs were detected in all samples with concentra ons ranging from 857 to 25,462 items km -2 . The majority of microplas cs analysed were fragments of polyethylene, polypropylene and polystyrene in the size range 1,000 to 5,000 µm. Mesoplas cs (>5,000 µm) mainly in the form of filaments were found with concentra ons ranging from 0 to 2,139 items km -2 and macroplas cs (>5,000 µm) in the form of fragments and filaments were also found with concentra ons ranging from 0 to 1,078 items km -2 . These fragments and filaments likely originate from the break-up of common macroli er items in the environment, such as plas c bags, bo les and fishing gears which are commonly comprised of similar polymers to those found in the present study. Our findings demonstrate that li er of all size classes are abundant in surface water, highligh ng that it is a key compartment for the transport of marine li er and should be monitored to be er our understanding of the fate and danger of plas c contamina on in our ocean.